A single rose - Barbery, Muriel, 1969- (Europa Editions, 2021)
Rose has turned 40, but has barely begun to live. When the Japanese father she never knew dies and she finds herself an orphan, she leaves France for Kyoto to hear the reading of his will. In the days before Haru's last wishes are revealed, his former assistant, Paul, takes Rose on a tour of the temples, gardens and eating places of this unfamiliar city. Initially a reluctant tourist and awkward guest in her late father's home, Rose gradually comes to discover Haru's legacy through the itinerary he set for her, finding gifts greater than she had ever imagined. This stunning novel from international bestseller Muriel Barbery is a mesmerizing story of second chances, of beauty born out of grief and roses grown from ashes.